WAIVERS OF INFORMED CONSENT IN RESEARCH USING SECONDARY HEALTH DATA: ETHICAL AND LEGAL GAPS IN VIETNAM (Vietnam Journal of Community Medicine, 2026)
Background: Secondary health data are highly valuable for biomedical research but raise significant challenges regarding patients’ informed consent. While international ethical standards allow conditional waivers of informed consent, Viet Nam’s ethical and legal framework lacks clear and consistent regulations, leading to variability in ethical review practices across research institutions and ethics committees.Objective: To analyze the current ethical and legal framework in Viet Nam and compare it with international standards on waivers of informed consent in research using secondary health data, with the aim of proposing solutions to improve research policy and practice.Methods: Narrative literature review.Results: Searched and analyzed 12 legal documents related to waivers of informed consent in research using secondary health data including: Constitution, Laws, Decrees, Circulars, and international documents.Conclusion: Waivers of informed consent in research using secondary health data are recognized in international ethical standards as conditional exceptions. However, in Viet Nam, the ethical and legal framework governing this practice remains fragmented, with a lack of clear definitions and application criteria. This gap leads to inconsistencies in ethical review and poses potential risks to patients’ privacy and the trust of patients and the wider community.Recommendations: The ethical and legal framework for waivers of informed consent should be strengthened by standardizing clear ethical criteria, particularly regarding the impracticability of re-consent and minimal risk, while clearly defining the role of Ethics Committees as entities for ethical and data governance in research using secondary health data, thereby progressively ensuring harmonization between Vietnamese law and international standards.
Keywords: Waivers of informed consent, Secondary health data, Ethical-legal gaps.